Efisiensi Biosorpsi Logam Cu(II) Oleh Biomassa Coprinus Comatus Teraktivasi H2SO4 - Pope Jessica Sirait; Elvi Yenie; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Heavy metal Cu(II) which contained in electroplating wastewater is a highly toxic substance and very dangerous for living creatures. The toxicity that these metals carry can lead to chronic, acute, and cancer-causing poisoning. Biosorption with fungi is one of the abatement methods to reduce the metal contaminant in environment. The present study aimed at determining the maximum biosorption capacity and the removal percentage of Cu(II) biosorption by Coprinus comatus. Empty Fruit Bunches(EFB) is used as growing medium of Coprinus comatus then used to adsorb a solution containing heavy metal Cu(II) with concentration 1,62 ppm. The adsorbed metal ion was calculated from metal ion concentration after activated by H2SO4 with variation concentration based on the analysis with Atomic Absorption Spectrophotometry (AAS) method. The result showed that Cu(II) not effectively adsorbed by Coprinus comatus activated by H2SO4 as the biosorbent. Keywords : Biosorption, Coprinus comatus, Activated, H2SO4, Electroplating